Investigating digitized authentic materials: Pre-service teachers’ voice - Adriani Yulia Purwaningrum; Fazri Nur Yusuf (Universitas Islam Sultan Agung, 2020)
Over past few decades, research on authentic materials has been focused on helping teachers provide their learners’ teaching materials. Most of the researches in this area explore the benefits and drawbacks of authentic materials utilization in the classroom. This multiple case study aims at investigating benefits of and barriers in using authentic materials presented as a digital media used in their EFL classrooms. Document and an interview were employed to reveal the teachers’ perception. The findings indicate although it was considered difficult to find and organize, digitized authentic materials helped teachers in teaching English as a Foreign Language for learners with various levels and backgrounds. Its use could help teachers motivate and promote their students’ interest in learning. However, disselection and misuse of it might not meet students’ needs and interest in learning. Good teachers’ capacity in finding and using the digitized authentic materials could encourage better learning process and students’ better learning achievement. Therefore, it is recommended that for the further study, learners’ perception also need to be explored.